2006
DOI: 10.1541/ieejias.126.255
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Generator System Selection for Large Wind Turbine Generator System

Abstract: This paper focuses on selection of wind turbine generation systems that include generators, converters and gears. We study Fig. 1): permanent magnet generator (PMG) system, doubly-fed generator (DFG) system and synchronous generator (SYG) system in terms of the system efficiencies and running costs. Figure 2 shows flow chart for estimation of system efficiency. The system efficiencies are calculated with considering mechanical loss, iron loss, copper loss, and stray loss of three types generator systems. Figu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Another comparative study of these wind turbine drive train topologies at 5 MW level has been reported in [11], which also shows that the total mass of the DD PMG is almost 50% of that of the DD EESG, while the PMG 1G is 10 times lighter than the DD EESG. The results from these two separate studies seem to correlate well.…”
Section: Comparison Of Direct-drive and Geared Generator Conceptsmentioning
confidence: 94%
See 1 more Smart Citation
“…Another comparative study of these wind turbine drive train topologies at 5 MW level has been reported in [11], which also shows that the total mass of the DD PMG is almost 50% of that of the DD EESG, while the PMG 1G is 10 times lighter than the DD EESG. The results from these two separate studies seem to correlate well.…”
Section: Comparison Of Direct-drive and Geared Generator Conceptsmentioning
confidence: 94%
“…The results from these two separate studies seem to correlate well. An interesting finding from [11] is that the PMG 1G tends to have a higher power generation capacity than that of the DFIG at a lower wind speed site. This implies that the PMG 1G is likely a better option for countries where average wind speeds are relatively low (e.g.…”
Section: Comparison Of Direct-drive and Geared Generator Conceptsmentioning
confidence: 99%